Therapeutic effects of KRM-II-81, positive allosteric modulator for α2/3 subunit containing GABAA receptors, in a mouse model of Dravet syndrome - Nakakubo, Sachiko; Hiramatsu, Yasuyoshi; Goto, Takeru; Kimura, Syuhei; Narugami, Masashi; Nakajima, Midori; Ueda, Yuki; Shiraishi, Hideaki; Manabe, Atsushi; Sharmin, Dishary; Cook, James M.; Egawa, Kiyoshi (Frontiers in Pharmacology, 2023)
【Introduction】Dravet syndrome (DS) is an intractable epilepsy syndrome concomitant with neurodevelopmental disorder that begins in infancy. DS is dominantly caused by mutations in the SCN1A gene, which encodes the α subunit of a voltage-gated Na channel. Pre-synaptic inhibitory dysfunction is regarded as the pathophysiological mechanism, but an effective strategy for ameliorating seizures and behavioral problems is still under development. Here, we evaluated the effects of KRM-II-81, a newly developed positive allosteric modulator for α 2/3 subunit containing GABAA receptors (α2/3-GABAAR) in a mice model of DS both in vivo and at the neuronal level. 【Methods】We used knock-in mice carrying a heterozygous, clinically relevant SCN1A mutation (background strain: C57BL/6J) as a model of the DS (Scn1a WT/A1783V mice), knock-in mouse strain carrying a heterozygous, clinically relevant SCN1A mutation(A1783V). Seizure threshold and locomotor activity was evaluated by using the hyperthermia-induced seizure paradigm and open filed test, respectively. Anxiety-like behavior was assessed by avoidance of the center region in locomotor activity. We estimated a sedative effect by the total distance traveled in locomotor activity and grip strength. Inhibitory post synaptic currents (IPSCs) were recorded from a hippocampal CA1 pyramidal neuron in an acutely prepared brain slice. 【Results】KRM-II-81 significantly increased the seizure threshold of Scn1a WT/A1783V mice in a dose-dependent manner. A low dose of KRM-II-81 specifically improved anxiety-like behavior of Scn1a WT/A1783V mice. A sedative effect was induced by relatively high dose of KRM-II-81 in Scn1a WT/A1783V mice, the dose of which was not sedative for WT mice. KRM-II-81 potentiated IPSCs by increasing its decay time kinetics. This effect was more prominent in Scn1a WT/A1783V mice. 【Discussion】Higher activation of α2/3-GABAAR by KRM-II-81 suggests a compensatory modification of post synaptic inhibitory function against presynaptic inhibitory dysfunction in Scn1a WT/A1783V . The increased sensitivity for KRM-II-81 may be relevant to the distinct dose-dependent effect in each paradigm of Scn1a WT/A1783V mice. 【Conclusion】 Selective activation forα2/3-GABAAR by KRM-II-81 could be potential therapeutic strategy for treating seizures and behavioral problems in DS.